Analisis Persepsi Dukungan Organisasi dan Kepuasan Kerja Kaitannya dengan Komitmen Organisasi pada PT. Mimoza Multimedia Gorontalo - Musafir Musafir (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2021)
This study aims to analyze the effect of perceived organizational support and job satisfaction on organizational commitment at PT. Mimoza Multimedia Gorontalo. The data collection technique used the census method on 97 employees by distributing questionnaires. The analytical method used is the path analysis method (Path Analysis). The results of testing the first hypothesis show that the perceived variable of organizational support and job satisfaction simultaneously has a positive and significant effect on organizational commitment with a contribution (R-Square) of 45.2%. Then testing the second hypothesis shows that the variable perception of organizational support partially has a positive and significant effect on organizational commitment with a partial contribution of 28.4%. Meanwhile, testing the third hypothesis shows that the job satisfaction variable partially has a positive and significant effect on organizational commitment with a coefficient of 16.8%